Porous alumina and catalyst

By adding an appropriate amount of silicate and barium oxide to γ-alumina, the specific surface area reduction and carbon deposition at high temperatures are solved, and the thermal stability and coking resistance of the catalyst are improved.

JP2025019168AActive Publication Date: 2025-02-06RENAISSANCE ENERGY RES +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024202884
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2024-11-21
Publication Date
2025-02-06
Estimated Expiration
2041-02-18

AI Technical Summary

Technical Problem

Traditional gamma-alumina materials are easily converted to α phase at high temperatures, resulting in a decrease in specific surface area and more significant transformation under water vapor atmosphere and high pressure. At the same time, their solid acidity increases, resulting in carbon deposition on the surface of the catalyst and catalyst deactivation.

Method used

By adding silicate and barium oxide as solid alkali oxides in γ-alumina, the addition ratio is controlled so that it maintains a large specific surface area at high temperatures and reduces solid acidity, thereby inhibiting α-phase transformation and carbon deposition.

Benefits of technology

Maintaining a large specific surface area at high temperatures and inhibiting carbon deposition, improving the thermal stability and coking resistance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019168000001
    Figure 2025019168000001
  • Figure 2025019168000002
    Figure 2025019168000002
  • Figure 2025019168000003
    Figure 2025019168000003
Patent Text Reader

Abstract

To provide a porous alumina excellent in heat resistance and coking resistance.SOLUTION: A porous alumina includes an aluminum oxide with a silica and a barium oxide added. The silica and the barium oxide are added to the aluminum oxide so that, if a SiO2 addition rate (mass%) is a rate of SiO2 added with regard to total mass of the aluminum oxide and the SiO2 added, and a BaO addition rate (mass%) is a rate of BaO added with regard to total mass of the aluminum oxide and the SiO2 added, within a range of the SiO2 addition rate 3 mass% or lower and the BaO addition rate 14 mass% or lower, a specific surface area measured by a prescribed measuring method after heat treatment at 1200°C for 30 hours of the porous alumina is equal to or higher than a reference specific surface area measured in a similar manner of a reference porous alumina for comparison with the SiO2 addition rate 3 mass% and the BaO addition rate 0 mass%, set to the porous alumina.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to porous alumina obtained by adding silica and a solid basic oxide to aluminum oxide, and a catalyst using porous alumina as a catalyst support, and in particular to porous alumina and a catalyst to which barium oxide is added as a solid basic oxide. [Background technology]

[0002] Porous alumina materials having a large specific surface area, such as γ-alumina, are useful as catalyst supports for supporting catalytic substances, filters, and the like, and efforts have been made to improve their properties (see, for example, Patent Documents 1 to 5, etc.). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-203654 A [Patent Document 2] International Publication No. 2014 / 051091 [Patent Document 3] International Publication No. 2012 / 096386 [Patent Document 4] International Publication No. 2013 / 111457 [Patent Document 5] JP 2009-061383 A [Non-patent literature]

[0004] [Non-Patent Document 1] Toru Numaguchi et al., "Evaluation of activity and carbon deposition of methane steam reforming catalysts," Journal of the Petroleum Society, Vol. 39, No. 3, 1996. [Non-Patent Document 2] Ki-Yong Lee, et al., "Deactivation by coke deposition on the HZSM-5 catalysts in the methanol-to-hydrocarbon conversion", Journal of Physics and Chemistry of Solids 73 (2012) 1542-1545. Summary of the Invention [Problem to be solved by the invention]

[0005] However, conventional porous alumina materials with large specific surface areas, such as γ-alumina, easily transition to the α phase and significantly reduce their specific surface area when heated to temperatures of 1000°C or higher for a very short time, or even at lower temperatures for a long time. The transition to the α phase tends to be even more pronounced in a water vapor atmosphere or under high pressure.

[0006] To suppress the transition to the α phase, silica (SiO 2 When a solid acidic additive such as ethylenediaminetetraacetate is used, the heat resistance is significantly improved and a large specific surface area can be maintained even at high temperatures, but the solid acidity of the porous alumina material increases. Therefore, when a porous alumina material containing a solid acidic additive is used as a catalyst support, carbon deposition (coking) is likely to occur on the catalyst surface in a reaction targeting hydrocarbons, which causes catalyst deactivation. Therefore, catalyst supports used in reactions using hydrocarbons, such as steam reforming reactions, are required to have not only heat resistance but also coking resistance. It is well known that as the solid acidity of a porous support increases, coking is more likely to occur, as disclosed in the above-mentioned Non-Patent Documents 1 and 2.

[0007] Fig. 1 shows the SiO2 of porous alumina containing only silica, which was prepared by the same kneading method as the comparative sample described later. 2The relationship between the addition rate and the specific surface area is shown in Fig. 1. The specific surface area of ​​each of sample A, which was obtained by firing in air at 1000°C for 5 hours, sample B, which was obtained by additionally heat-treating sample A at 1200°C for 5 hours, and sample C, which was obtained by additionally heat-treating sample A at 1200°C for 30 hours, was measured by the nitrogen adsorption BET method. As shown in Fig. 1, the SiO 2 As the addition rate increases, the specific surface area after heat treatment increases significantly, indicating that silica is effective in improving the heat resistance of porous alumina. It is clear that this is effective.

[0008] Figure 2 shows the thermal desorption spectrometry (TPD, base probe molecule: NH 3 , acid probe molecule: CO 2 ) shows the results of measuring the amount of solid acid and the amount of solid base on the surface of porous alumina. 2 With increasing addition rate, NH 3 The amount of adsorption increases, and CO 2 It can be seen that the amount of adsorption decreases, the amount of solid acid on the surface of the porous alumina increases, and the amount of solid base decreases.

[0009] The acid and base sites on the solid surface are difficult to neutralize, so they coexist. Silica, alumina, and their mixed oxides are both solid acids and solid bases, so as shown in Figure 2, both the amount of solid acid and the amount of solid base are measured without being neutralized on the solid surface.

[0010] 1 and 2, it is clear that it is difficult to improve the heat resistance of γ-alumina while suppressing the increase in solid acidity (coking resistance) by simply adding solid acidic silica. In addition, methods have been reported in which barium, lanthanum, or the like is added to alumina for the purpose of improving heat resistance, but none of these methods can be said to have sufficient heat resistance (see Patent Documents 4 and 5).

[0011] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide a porous alumina having excellent heat resistance and coking resistance, and further to provide a catalyst using the porous alumina as a catalyst support. [Means for solving the problem]

[0012] The present inventors have, as a result of extensive research, discovered that by combining silica with barium oxide, which is a solid basic oxide, as an additive to be added to porous alumina having a large specific surface area, such as γ-alumina, and appropriately adjusting the amounts of silica and barium oxide added, it is possible to obtain porous alumina that has better heat resistance and coking resistance than porous alumina to which only silica is added, and have arrived at the invention described below.

[0013] Aluminum oxide (Al 2 O 3 ) to silica (SiO 2 ) and barium oxide (BaO) are added to the porous alumina, The aluminum oxide and SiO 2 The amount of SiO relative to the total mass of the added 2 The ratio of the added amount is SiO 2 The addition rate (mass%) is The aluminum oxide and the SiO 2 The ratio of the amount of BaO added to the total amount of added BaO is the BaO addition rate (mass%). The SiO 2 The amount of addition is determined by dividing the content of silicon (Si) in the porous alumina by SiO 2 This is the amount converted into the content of The BaO content is the amount of barium (Ba) in the porous alumina converted into the BaO content, The SiO 2 The BaO content is in the range of 3 mass% or less, and the BaO content is in the range of 14 mass% or less, The specific surface area of ​​the porous alumina measured by a predetermined measuring method after heat treatment at 1200° C. for 30 hours is 2 The specific surface area of ​​the porous alumina was determined so as to be equal to or larger than the specific surface area of ​​the standard porous alumina for comparison, in which the BaO content was set to 3% by mass and the BaO content was set to 0% by mass. The first feature is that the silica and the barium oxide are added to the aluminum oxide.

[0014] Incidentally, the specific surface area is naturally measured by the same method for the porous alumina according to the present invention and the reference porous alumina for comparison. For example, the well-known nitrogen adsorption BET method similar to that used for measuring the specific surface area shown in FIG. 1 can be used.

[0015] In addition, SiO 2 The amount of addition determines the content of silicon (Si) in the porous alumina as SiO 2 and the amount of barium added is specified as the amount obtained by converting the barium (Ba) content in porous alumina into the BaO content. However, these specifications take into consideration the fact that, in the prepared porous alumina, the amounts of each addition are measured by an X-ray fluorescence analyzer as the amounts of silicon and barium element, not as the amounts of silica and barium oxide added, and further, that when a part of the added silica enters the alumina skeleton as silicon, the added silica and barium oxide may form an aluminate phase through a solid-phase reaction with alumina.

[0016] According to the first characteristic of the porous alumina, SiO 2 When the BaO content is within a range of 3% by mass or less, and when the BaO content is within a range of 14% by mass or less, the solid acidity is equal to or less than the reference solid acidity, and 2 The addition rate and BaO addition rate are set so that the specific surface area after heat treatment at 1200°C for 30 hours is equal to or greater than the reference specific surface area, and therefore, for the reasons explained below, a porous alumina having better heat resistance and coking resistance than a porous alumina containing only silica added can be obtained.

[0017] First, SiO 2 was used as a standard porous alumina for evaluating heat resistance and coking resistance. 2 The reason for using porous alumina with the BaO doping rate of 3 mass % and the BaO doping rate of 0 mass %, respectively, will be explained.

[0018] Figure 3 shows the SiO 2The porous alumina support had a BaO content of 0.5% to 20% by mass, and the BaO content was 0% by mass. 2 O 3 The figure shows the results of evaluating the amount of coking when a steam reforming reaction was carried out on a steam reforming catalyst carrying 10% by mass of carbon black (calculated as 10% by mass).

[0019] The porous alumina was prepared in the same manner as the comparative sample having a BaO addition rate of 0 mass % prepared by the kneading method described below.

[0020] The steam reforming catalyst was prepared by the impregnation method as follows: the porous alumina was impregnated with a mixed aqueous solution of nickel nitrate and lanthanum nitrate at room temperature for 1 hour, and then evaporated to dryness using an evaporator. After solidification, it was calcined for 5 hours at 450° C. The powder catalyst supporting Ni-La was pressure molded using a press, pulverized in a mortar until it became granular, and sieved to size between 180 μm and 250 μm.

[0021] The steam reforming reaction was carried out as follows. 0.5 ml of the catalyst was weighed in a measuring cylinder and placed in a stainless steel reaction tube. The catalyst was pretreated by reduction treatment in a hydrogen stream at 600°C for 1 hour. 3 H 8 : 60ml / min, N 2 : 60ml / min, H 2 : 6ml / min, H 2 The steam reforming reaction was carried out at a flow rate of O: 360 ml / min. The reaction conditions were S / C = 2.0, SV = 60,000 h -1 The temperature was raised from room temperature at a rate of 10°C / min, and when it reached 600°C, it was held for 43 minutes. The product gas was sampled and its composition was analyzed by gas chromatography.

[0022] The amount of coking was measured using a carbon and sulfur analyzer (CS-200, manufactured by LECO Japan LLC). A sample of 0.03g of the catalyst sample that underwent steam reforming reaction and 1g of a fuel improver (tin-plated copper) were mixed and placed in a crucible, and the carbon in the sample was burned in a high-frequency combustion furnace using oxygen as a carrier gas (flow rate 3L / min). The carbon gasified by high-temperature combustion was detected by infrared absorption, and the amount of carbon was measured.

[0023] Figure 4 shows the SiO 2 Attachment The five samples (indicated by ●) of porous alumina with BaO addition in the range of 0 mass% to 5 mass%, and 0 mass% of porous alumina with BaO addition, and the SiO 2 The results of measuring the phase transition temperature to the α phase using one sample (indicated by a circle) of porous alumina with an additive rate of 1 mass % and a BaO additive rate of 5 mass % are shown.

[0024] The phase transition temperature was measured using a thermogravimetric analyzer (Rigaku, differential thermobalance, Thermo A 20 mg sample was placed in a platinum pan and heated at a rate of 20°C / min from room temperature. An exothermic reaction was observed when alumina undergoes a phase transition from δ,θ-alumina to α-alumina. The exothermic peak temperature in the differential thermal analysis (DTA) curve was determined as the phase transition temperature.

[0025] From the measurement results of the amount of coking shown in Fig. 3, SiO 2 When the addition rate was 3 mass% or less, almost no coking occurred, whereas when the SiO 2 When the addition rate is increased beyond 3 mass%, SiO 2 It can be seen that the amount of coking increases roughly in proportion to the addition rate.

[0026] From the measurement results of the phase transition temperature shown in FIG. 4, when the BaO addition rate is 0 mass%, SiO 2As the addition rate increases from 0 mass%, 1 mass%, 2 mass%, 3 mass%, and 5 mass%, the phase transition temperature increases from 1201°C to 1282°C, 1290°C, 1396°C, and 1416°C, respectively, and SiO 2 It can be seen that the heat resistance improves with increasing SiO 2 As the addition rate increases from 0 to 3 mass%, the phase transition temperature increases by 195°C, from 1201°C to 1396°C, whereas the SiO 2 When the addition rate increases from 3 mass% to 5 mass%, the phase transition temperature increases by only 20°C, from 1396°C to 1416°C. 2 The improvement in heat resistance with increasing the addition rate is 2 This is particularly evident when the addition rate is 3 mass % or less. The measurement results in FIG. 4 coincide with the relationship shown in FIG.

[0027] On the other hand, SiO 2 Comparing two samples with an additive rate of 1 mass% and BaO additive rates of 0 mass% and 5 mass%, it can be seen that when the BaO additive rate increases from 0 mass% to 5 mass%, the phase transition temperature increases by 129°C, from 1282°C to 1411°C.

[0028] From the measurement results shown in Figs. 3 and 4, SiO 2 By limiting the addition rate to 3 mass% or less, the increase in the amount of coking is suppressed while SiO 2 It is clear that when the BaO addition rate is 3 mass % or less, the heat resistance can be significantly improved by setting the BaO addition rate within a predetermined preferred range including 5 mass %.

[0029] From the above explanation, SiO 2 It can be seen that the porous alumina with the SiO and BaO addition rates of 3 mass% and 0 mass% (reference porous alumina) have a certain degree of heat resistance and coking resistance. 2 If the addition rate is less than 3 mass%, the heat resistance decreases. 2 If the addition rate is increased beyond 3 mass%, the coking resistance decreases. 2The addition rate of 3 mass% is a singular point where heat resistance and coking resistance can be achieved simultaneously. In other words, it is practically impossible for porous alumina to which only silica is added to achieve both heat resistance and coking resistance that exceed those of the standard porous alumina. Therefore, when attempting to improve both heat resistance and coking resistance in porous alumina to which both silica and barium oxide are added compared to porous alumina to which only silica is added, the standard porous alumina can be said to be appropriate as an evaluation standard for heat resistance and coking resistance.

[0030] The effect of improving heat resistance by adding barium oxide in addition to silica can be explained as follows.

[0031] The ionic radius of Si is almost the same as that of aluminum (Al), and Si ions are incorporated into the structure of γ-alumina by the decomposition of the alumina precursor at around 450°C. In γ-alumina with a spinel structure, there are many vacancies in the octahedral sites. By adding Si ions to alumina, the Al ions in the tetrahedral sites are replaced by Si ions, reducing the total number of vacancies, suppressing the formation of alpha phases and improving heat resistance. In addition, the addition of silica is effective in preventing the blocking of alumina micropores, and is effective in improving heat resistance in the temperature range below 1100°C.

[0032] Ba ions react with alumina at high temperatures of over 1000°C to form aluminate (barium hexaaluminate: BaO 6Al 2 O 3 , Barium monoaluminate: BaO·Al 2 O 3 ) (See Figures 9 and 10). Aluminates are formed on the surface of alumina particles and suppress the alpha phase inside the alumina particles. The aluminates on the particle surface are cubic (fcc) and have the same structure as gamma alumina, so a strong interaction occurs by sharing oxygen ions on the alumina particle surface. This interaction suppresses the alpha phase inside the alumina particles.

[0033] When Ba is added alone to alumina, it is necessary to generate aluminate based on a solid-phase reaction. For this purpose, calcination at 1000°C or higher is required, and the alumina loses its micropores and the specific surface area is significantly reduced because the alpha phase is not suppressed during the temperature rise process before the aluminate is generated. However, alumina containing silica can suppress the blockage of micropores and the decrease in the specific surface area in the temperature range of 1100°C or less during the temperature rise process before the aluminate is generated due to the effect of adding silica. Furthermore, at high temperatures above this temperature range, aluminate is generated by a solid-phase reaction of Ba, and the alpha phase of alumina is suppressed.

[0034] In addition, a given SiO 2 As will be described later, it has been confirmed through intensive research by the present inventors that, when the BaO doping rate is increased from 0 mass% within a range of 14 mass% or less, the specific surface area after heat treatment at 1200°C for 30 hours increases beyond the standard specific surface area, and when it exceeds the maximum value, it decreases toward the standard specific surface area (see Figs. 11 and 14). 2 When the doping rate is within the range of 3 mass% or less and the BaO doping rate is within the range of 14 mass% or less, the specific surface area after heat treatment at 1200°C for 30 hours is equal to or greater than the reference specific surface area, that is, the specific surface area of ​​the standard porous alumina (SiO 2 Addition rate: 3 mass%, BaO addition rate: 0 mass%) improves heat resistance. 2 There is certainly a combination of the additive rate and the BaO additive rate, and by adopting this combination, the heat resistance is certainly improved.

[0035] In addition, the SiO 2 From the relationship between the doping rate and the BaO doping rate and the solid acidity, a given SiO of 3 mass% or less 2 It can be seen that when the BaO addition rate is increased, the amount of solid acidity decreases monotonically (solid acidity decreases). Therefore, as described above, the relationship that the more the solid acidity of the porous carrier increases, the more likely coking occurs. 2By suppressing the addition rate to 3 mass% or less and further increasing the BaO addition rate, the increase in the amount of coking is further suppressed, and the coking resistance is improved. 2 The combination of BaO and CrO addition rates also ensures improved coking resistance.

[0036] Therefore, when only silica is added, it is difficult to achieve both heat resistance and coking resistance. However, by reducing the amount of silica added and adding barium oxide in addition to silica, it is possible to significantly improve both heat resistance and coking resistance compared to when only silica is added.

[0037] Furthermore, the porous alumina according to the first aspect of the present invention is characterized in that the SiO 2 It is preferable that the silica and the barium oxide are each added to the aluminum oxide at an addition rate within a range of 0.7 mass % or more and 3 mass % or less so that the specific surface area of ​​the porous alumina is equal to or greater than the reference specific surface area.

[0038] Furthermore, in the porous alumina according to the first characteristic, it is preferable that the silica and the barium oxide are added to the aluminum oxide so that the specific surface area of ​​the porous alumina is equal to or greater than the reference specific surface area, and the BaO addition rate is within a range of 0.5 mass % to 14 mass %.

[0039] According to a preferred embodiment of the porous alumina of the first aspect, SiO 2 When the BaO content is within the range of 0.7 mass% or more and 3 mass% or less, or when the BaO content is within the range of 0.5 mass% or more and 14 mass% or less, both the heat resistance and the coking resistance are improved. 2 Therefore, the combination of the addition rate and the BaO addition rate is more likely to exist.

[0040] Furthermore, the porous alumina according to the first aspect of the present invention is characterized in that the SiO 2 When the additive rate is Xs (mass%) and the BaO additive rate is Xb (mass%), A second feature is that 0.7 mass%≦Xs<1 mass%, and 5 mass%≦Xb≦10 mass%, or 1 mass%≦Xs<2 mass%, and 3 mass%≦Xb≦10 mass%, or 2 mass%≦Xs≦3 mass%, and 1 mass%≦Xb≦14 mass%.

[0041] Furthermore, the porous alumina according to the present invention is made of aluminum oxide (Al 2 O 3 ) to silica (SiO 2 ) and barium oxide (BaO) are added to the porous alumina, The aluminum oxide and SiO 2 The amount of SiO relative to the total mass of the added 2 SiO defined by the ratio of added amount 2 The addition rate (mass%) is Xs (mass%), where 2 The amount of addition is determined by dividing the content of silicon (Si) in the porous alumina by SiO 2 This is the amount converted into the content of The aluminum oxide and the SiO 2 When the BaO addition rate (mass%) defined as the ratio of the BaO addition amount to the total mass of the addition amounts is Xb (mass%), the BaO addition amount is the amount obtained by converting the content of barium (Ba) in the porous alumina into the content of BaO, A third feature is that 0.7 mass%≦Xs<1 mass%, and 5 mass%≦Xb≦10 mass%, or 1 mass%≦Xs<2 mass%, and 3 mass%≦Xb≦10 mass%, or 2 mass%≦Xs≦3 mass%, and 1 mass%≦Xb≦14 mass%.

[0042] According to the porous alumina of the second or third aspect, SiO 2 Within the ranges of the doping rate Xs and the BaO doping rate Xb, the standard porous alumina (SiO 2 Compared with the case where the BaO content is 3 mass % and the BaO content is 0 mass %, both the heat resistance and the coking resistance are reliably improved.

[0043] Furthermore, the porous alumina having the second or third characteristic preferably satisfies 1 mass%≦Xs≦3 mass% and 3 mass%≦Xb≦10 mass%.

[0044] According to a preferred embodiment of the porous alumina having the second or third aspect, both the heat resistance and the coking resistance can be further improved.

[0045] Furthermore, the catalyst according to the present invention is characterized by comprising the porous alumina according to the first or second aspect above, and a catalytic substance supported on the porous alumina.

[0046] The catalyst having the above characteristics has improved heat resistance and coking resistance compared to conventional catalysts that use porous alumina as a carrier. Effect of the Invention

[0047] According to the porous alumina of the present invention, the use of barium oxide, which is a solid basic oxide, makes it possible to obtain a porous alumina having a high molecular weight. By appropriately adjusting the amounts of silica and barium oxide added, it is possible to provide a high heat resistance that can maintain a large specific surface area even at high temperatures, while suppressing the amount of silica added and suppressing an increase in the amount of solid acid, thereby realizing high coking resistance and providing a high-performance porous alumina that is excellent in both heat resistance and coking resistance. Furthermore, by using the porous alumina as a catalyst carrier, it is possible to provide a catalyst that is excellent in both heat resistance and coking resistance. [Brief description of the drawings]

[0048] [Figure 1] A diagram showing the relationship between the SiO2 addition rate and the specific surface area of ​​porous alumina to which only silica has been added under three different heat treatment conditions. [Diagram 2] A graph showing the results of measuring the SiO2 loading rate and the solid acid and solid base amounts of porous alumina to which only silica was added. [Diagram 3]Figure showing the results of measuring the SiO2 loading rate and the amount of coking in a steam reforming catalyst in which Ni-La is supported on porous alumina to which only silica is added. [Figure 4] FIG. 1 shows the results of measuring the phase transition temperature to the α phase in porous alumina to which only silica has been added, and in porous alumina to which silica and barium oxide have been added. [Diagram 5] A process flow diagram showing an overview of the method for preparing porous alumina according to the present invention using a kneading method. [Figure 6] A process flow diagram showing an overview of the method for preparing porous alumina according to the present invention by the first type of impregnation method. [Figure 7] A process flow diagram showing an overview of the method for preparing porous alumina according to the present invention by the second type of impregnation method. [Figure 8] A diagram showing the measurement results of the specific surface area of ​​evaluation samples and comparison samples prepared by the kneading method under three different heat treatment conditions. [Figure 9] Graph showing XRD diffraction patterns showing the crystal structures of evaluation samples and comparative samples prepared by the kneading method under three different heat treatment conditions. [Figure 10] 10 is a graph showing an XRD diffraction pattern illustrating the crystal structure of the evaluation sample shown in FIG. [Figure 11] A table showing the measurement results of the specific surface area of ​​multiple evaluation samples and comparison samples with different SiO2 and BaO addition rates prepared by the kneading method after heat treatment at 1200°C for 30 hours. [Figure 12] FIG. 1 shows the results of measuring the solid acid amount and solid base amount of an evaluation sample and a comparative sample prepared by a kneading method. [Figure 13] FIG. 1 shows the results of measuring the solid acidity of a number of evaluation samples and comparative samples with different SiO2 and BaO addition rates prepared by the kneading method. [Figure 14] A table showing the measurement results of the specific surface area of ​​multiple evaluation samples and comparison samples with different SiO2 and BaO addition rates prepared by the first type of impregnation method after heat treatment at 1200°C for 30 hours. [Figure 15]FIG. 1 shows the results of measuring the solid acidity of a number of evaluation samples and comparative samples with different SiO2 and BaO addition rates prepared by the first type of impregnation method. [Figure 16] A process flow diagram showing an overview of the method for preparing porous alumina according to the present invention by a precipitation method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0049] A preferred embodiment of the porous alumina according to the present invention (hereinafter, appropriately referred to as "the present embodiment") will be described.

[0050] The porous alumina according to the present embodiment (hereinafter, appropriately referred to as "the present alumina") is alumina (aluminum oxide, Al 2 O 3 ) to silica (SiO 2 It is a porous alumina to which two types of oxides, SiO2 (SiO2) and barium oxide (BaO), have been added. In the following explanation, "this alumina" refers to , is an alumina to which silica and barium oxide have been added, and when simply referred to as "alumina", it is an alumina to which silica and barium oxide have not been added.

[0051] [1] Preparation method of this alumina: Next, the preparation method of the present alumina will be described. The preparation method of the present alumina is basically configured to include a process for adding silica to alumina and a process for adding barium oxide to alumina. The preparation method may be an impregnation method, a kneading method, a precipitation method, a sol-gel method, etc., depending on the difference in the process for adding barium oxide. In this embodiment, the kneading method and the impregnation method are used in the preparation of samples for evaluating the heat resistance and coking resistance of the present alumina.

[0052] Before describing the details of the kneading method and the impregnation method, the respective addition rates of silica and barium oxide added to the alumina in this embodiment are defined as follows. 2 The units of the additive rate and the BaO additive rate are "mass %."

[0053] SiO 2 Addition rate=SiO 2 Amount added / (mass of alumina + SiO 2 Addition amount)×100 BaO addition rate = BaO addition amount / (mass of alumina + SiO 2 Addition amount)×100

[0054] SiO 2 The amount of addition is determined by dividing the Si content in the alumina by SiO 2 The amount of BaO added is the amount of Ba content in the present alumina converted into the BaO content. The Si content is the total content of Si present in the present alumina as a simple substance and a compound, and the Ba content is the total content of Ba present in the present alumina as a simple substance and a compound.

[0055] In this embodiment, SiO 2 The amount of BaO added is not included in the reference mass used to calculate the BaO content and BaO content because, in the method for preparing the present alumina described below, SiO 2 In setting the doping rate and BaO doping rate, (mass of alumina + SiO 2 It was more convenient to standardize the amount of SiO 2 The addition rate and BaO addition rate can be easily converted to an addition rate based on a reference mass including the amount of BaO added. In addition, the unit of each addition rate can be converted from "mass%" to "mol%" as necessary.

[0056] [1.1] Preparation of this alumina by kneading method: As shown in FIG. 5, the method for preparing the present alumina using the kneading method is roughly divided into the steps of: mixing an alkoxysilane solution containing an alkoxysilane, a mixed solvent containing water and an alcohol, and an inorganic acid with an aluminum solution containing an aluminum compound and water to prepare a mixed solution in which the aluminum compound and alkoxysilane are dissolved in the mixed solvent (step #K1); co-precipitating aluminum hydroxide with a silicon compound in the mixed solvent to form a precipitate (step #K2); adding an aqueous solution of a barium compound to the precipitate and kneading (step #K3); and drying and firing the precipitate kneaded with the barium compound to form a porous alumina (the present alumina) containing alumina, silica, and barium oxide (step #K4).

[0057] As the alkoxysilane contained in the alkoxysilane solution in step #K1, for example, tetraethoxysilane (hereinafter referred to as "TEOS") is preferably used, as the alcohol, for example, ethanol is preferably used, and as the inorganic acid, for example, hydrochloric acid or nitric acid is preferably used, but the present invention is not limited to these.

[0058] From the viewpoint of improving heat resistance, the aluminum solution in Step #K1 is preferably prepared by dissolving aluminum nitrate in water or by dissolving aluminum hydroxide in an aqueous solution of nitric acid.

[0059] The mixing ratio of the alkoxysilane and the aluminum compound in the mixed solution prepared in step #K1 is determined based on the silica addition rate (SiO 2 The addition rate is adjusted to the desired value.

[0060] The alkoxysilane and aluminum compound in the mixed solution prepared in step #K1 are uniformly dissolved in the mixed solvent composed of water and alcohol. In other words, the mixed solution forms a single liquid phase without phase separation.

[0061] In step #K2, a precipitant containing a basic compound is added to the acidic mixed solution while heating it preferably to 40°C to 100°C (for example, while heating and refluxing it at 100°C). By adding the basic compound until the pH of the mixed solution becomes about 8 (for example, 8 to 8.5), aluminum hydroxide and a silicon compound are coprecipitated. The silicon compound contained in the precipitate generated by coprecipitation may be an alkoxysilane or a hydrolysis condensate thereof.

[0062] The precipitating agent includes at least one basic compound selected from the group consisting of aqueous ammonia, sodium hydroxide, potassium hydroxide, and urea, of which aqueous ammonia is preferred.

[0063] In step #K3, the precipitate is preferably removed from the mixed solution by a normal method such as filtration, and washed with room temperature water (distilled water). An aqueous solution of a barium compound is added to the washed precipitate and kneaded. The aqueous solution of the barium compound is preferably prepared by dissolving barium nitrate in water to prepare a barium nitrate aqueous solution, or by dissolving barium hydroxide in water to prepare a barium hydroxide aqueous solution.

[0064] In step #K4, the precipitate kneaded with the barium compound is dried for a predetermined time in a dryer at 150°C, for example, and then the dried precipitate is pulverized into powder in a mortar, for example. The dried and powdered precipitate is fired in air at 1000°C for 5 hours, for example, to form porous alumina (the present alumina) containing alumina, silica, and barium oxide. In the porous alumina formed, the alumina is mainly composed of intermediate alumina such as γ-alumina and θ-alumina.

[0065] [1.2] Preparation of this alumina by impregnation method: There are two types of impregnation methods for preparing the present alumina: a first type in which silica and barium oxide are added to existing porous alumina by impregnation to prepare the present alumina; and a second type in which silica is added to alumina to prepare silica-added porous alumina, and barium oxide is then added to the silica-added porous alumina by impregnation to prepare the present alumina.

[0066] [1.2.1] The first type of impregnation method: As shown in Figure 6, the first type of impregnation method is roughly classified into two types: pre-made porous alumina (Al 2 O 3 The method includes the steps of: impregnating porous alumina (powder) with an alkoxysilane solution and an aqueous solution of a barium compound (Step #I11); and drying and firing the porous alumina impregnated with the alkoxysilane solution and the aqueous solution of a barium compound to form porous alumina containing alumina, silica, and barium oxide (the present alumina) (Step #I12).

[0067] The ready-made porous alumina used in step #I11 is a porous alumina mainly composed of intermediate aluminas such as γ-alumina and θ-alumina. For example, in the examples of this embodiment, C20 manufactured by Nippon Light Metal is used as the ready-made porous alumina, but it is not limited to the porous alumina manufactured by Nippon Light Metal, and an independently prepared one may also be used. In addition, the alkoxysilane contained in the alkoxysilane solution in step #I11 is a needle As in step #K1 of the kneading method, TEOS is preferably used. As in step #K3 of the kneading method, the aqueous solution of the barium compound in step #I11 is preferably prepared by dissolving barium nitrate in water to prepare an aqueous solution of barium nitrate, or by dissolving barium hydroxide in water to prepare an aqueous solution of barium hydroxide.

[0068] In step #I12, the porous alumina impregnated with the alkoxysilane solution and the aqueous solution of the barium compound is dried, for example, in air at 150°C or in a rotary evaporator, and then calcined, for example, in air at 1000°C for 5 hours to obtain porous alumina containing alumina, silica, and barium oxide (the present alumina).

[0069] [1.2.2] The second type of impregnation method: As shown in FIG. 7, the second type of impregnation method is roughly classified into a step of mixing an alkoxysilane solution containing an alkoxysilane, a mixed solvent containing water and an alcohol, and an inorganic acid with an aluminum solution containing an aluminum compound and water to prepare a mixed solution in which the aluminum compound and alkoxysilane are dissolved in the mixed solvent (step #I21); a step of co-precipitating aluminum hydroxide with a silicon compound in the mixed solvent to form a precipitate (step #I22); a step of drying and firing the precipitate to form a porous alumina containing alumina and silica (silica-added porous alumina) (step #I23); a step of impregnating the silica-added porous alumina with an aqueous solution of a barium compound (step #I24); and a step of drying and firing the silica-added porous alumina impregnated with the aqueous solution of the barium compound to form a porous alumina containing alumina, silica, and barium oxide (this alumina) (step #I25).

[0070] Steps #I21 and #I22 of the second type impregnation method are basically the same as steps #K1 and #K2 of the kneading method described above, and duplicated explanations will be omitted. Also, the preparation method of silica-added porous alumina in steps #I21 to #I23 is the same as the preparation method of a comparative sample with a BaO addition rate of 0 mass% by kneading method described later, except for the difference in the firing temperature in steps #K4 and #I23.

[0071] In the second type of impregnation method, the silica-added porous alumina used in step #I24 may be a ready-made silica-added porous alumina instead of the one prepared in steps #I21 to #I23.

[0072] In step #I23, the precipitate is preferably removed from the mixed solution by a normal method such as filtration, and washed with room temperature water (distilled water). The precipitate is dried to remove most of the solvent, and then pulverized in a mortar or the like to obtain a powder.

[0073] The dried and powdered precipitate is calcined to form silica-doped porous alumina, which is mainly composed of intermediate alumina such as γ-alumina and θ-alumina.

[0074] The firing temperature is preferably 400 to 1000° C. If the firing temperature is too high, the transition of aluminum oxide to the α phase may proceed, resulting in a decrease in the specific surface area. The firing time is preferably about one hour to several tens of hours.

[0075] In step #I24, similarly to step #K3 of the kneading method, the aqueous solution of the barium compound is preferably prepared by dissolving barium nitrate in water to prepare an aqueous barium nitrate solution, or by dissolving barium hydroxide in water to prepare an aqueous barium hydroxide solution.

[0076] In step #I25, similarly to step #I12 in the first type of impregnation method, the silica-added porous alumina impregnated with the aqueous solution of a barium compound is dried, for example, in air at 150°C or in a rotary evaporator, and then calcined, for example, in air at 1000°C for 5 hours to obtain porous alumina containing alumina, silica, and barium oxide (the present alumina).

[0077] The alumina prepared by the kneading method, the first or second type of impregnation method is mainly composed of intermediate alumina such as γ-alumina and θ-alumina. As an example, the alumina is in the form of powder obtained by crushing secondary particles formed by agglomeration of needle-like or fibrous primary particles and sieving the particles to a predetermined particle size range (for example, 100 μm to 500 μm). The shape of the alumina can be various, such as a powder, a pellet, a disk, or a honeycomb.

[0078] In the above kneading method, first or second type impregnation method, the amount of silicon and barium added to alumina is determined by the amount of each solution added. In other words, the total amount of silicon and barium in the added solution is added to alumina by evaporating the added solution to dryness. 2 The loading rate and BaO loading rate are uniquely determined by the mass of alumina or amount of alkoxysilane solution used and the amount of each solution added.

[0079] [2] Evaluation of heat resistance and coking resistance of this alumina prepared by the kneading method: [2.1] Preparation of evaluation samples and comparison samples: The evaluation samples were prepared by the kneading method shown in FIG. 5 as follows.

[0080] To prepare the alkoxysilane solution for step #K1, 7.52 g of ethanol was added to 5.00 g of TEOS and stirred at room temperature for 5 minutes, and then 1.25 g of hydrochloric acid (37% by mass) was added and stirred at room temperature for another 5 minutes. 71.23 g of water was added to this mixed solution to obtain a transparent, uniform 5.88% by mass TEOS solution.

[0081] In step #K1, the TEOS solution obtained in the above manner was added to a predetermined amount of 20% by mass aqueous aluminum nitrate solution to obtain a uniform mixed solution. 2The TEOS solution and aluminum nitrate aqueous solution were used in the amounts required for the addition rate. This mixed solution was heated to reflux, and 28% by mass ammonia water was dropped into it until the pH reached 8.5, and the solution was stirred. As the ammonia water was dropped, aluminum hydroxide and silicon compounds co-precipitated, and a precipitate was formed in the solution. This precipitate was filtered by suction filtration using No. 1 filter paper. This precipitate was washed with distilled water. A specified amount of barium nitrate aqueous solution was added to the washed precipitate and kneaded. Then, it was dried in a dryer at 150°C for 20 hours. The dried precipitate was crushed in a mortar and fired in air at 1000°C for 5 hours to obtain an evaluation sample of this alumina.

[0082] As a comparative sample, SiO 2 Only the additive rate is 0 mass%, only the additive rate of BaO is 0 mass%, SiO 2 Three comparative samples were also prepared, each with a 0% BaO content and a 0% BaO content. The evaluation samples and comparative samples are represented by the symbol SK(Xs, Xb). Xs is SiO 2 Xb indicates the BaO addition rate (mass%), and Xb indicates the BaO addition rate (mass%).

[0083] A comparative sample with Xs = 0% by mass was prepared by using a blank solution not containing TEOS (a solution containing ethanol and hydrochloric acid whose concentration was adjusted with water) instead of the TEOS solution in step #K1. A comparative sample with Xb = 0% by mass was prepared by omitting the step of adding an aqueous solution of a barium compound to the precipitate after suction filtration and water washing and kneading in step #K3.

[0084] [2.2] How to evaluate the samples: The specific surface area of ​​each sample was measured using a fully automatic gas aspiration meter under the following three heat treatment conditions: The nitrogen adsorption BET method was performed using a deposition measurement device (MicrotracBEL's BELSORP-max). The first heat treatment condition was the state before the other two types of heat treatments were performed (before heat treatment). The second heat treatment condition was the state after the temperature was raised from room temperature to 1200°C at 10°C / min, heating was stopped, and the temperature was held at 1200°C for 5 hours (1200°C 5 hours). The third heat treatment condition was the state after the temperature was raised from room temperature to 1200°C at 10°C / min, heating was stopped, and the temperature was held at 1200°C for 30 hours (1200°C 30 hours).

[0085] The crystal structure of each sample was measured by irradiating CuKα with an X-ray diffractometer (ULTIMA III, Rigaku) ​​and using a two-dimensional high-speed detector. The amounts of Al, Si, and Ba in each sample were measured by the glass bead method with an X-ray fluorescence analyzer (Supermini, Rigaku). The amount of solid acid and base in each sample was analyzed by temperature programmed desorption (TPD, base probe molecule: NH 3 , acid probe molecule :CO 2 ) was measured.

[0086] The sample evaluation method was the same as that for evaluating the heat resistance and coking resistance of the present alumina prepared by the first type of impregnation method described below.

[0087] [2.3] Heat resistance evaluation results: Figure 8 shows the results of measuring the specific surface area of ​​one evaluation sample and five comparison samples prepared by the kneading method before heat treatment, at 1200°C for 5 hours, and at 1200°C for 30 hours. The evaluation and comparison samples used were SK(1,7), SK(0,0), SK(1,0), SK(3,0), SK(5,0), and SK(0,7).

[0088] Figure 9 shows XRD diffraction patterns indicating the crystal structure of one evaluation sample and three comparative samples prepared by the kneading method before heat treatment, at 1200°C for 5 hours, and at 1200°C for 30 hours. The evaluation samples and comparative samples used were SK(1,7), SK(0,0), SK(1,0), and SK(0,7). Figure 10 shows the XRD diffraction patterns of the evaluation sample SK(1,7) shown in Figure 9 under the three types of heat treatment conditions in one graph.

[0089] Fig. 11 shows the results of measuring the specific surface area of ​​the evaluation samples and the comparative samples prepared by the kneading method after heat treatment at 1200°C for 30 hours by increasing the number of samples. The number of samples was 90 for the evaluation samples and 24 for the comparative samples. 2 The ranges of the addition rate and the BaO addition rate are wide, 0≦Xs≦30 and 0≦Xb≦100.

[0090] As shown in FIG. 8, in the comparative sample SK(0,7) to which only barium oxide was added, no significant improvement in the specific surface area was observed due to the addition of barium oxide, compared to the addition of silica, under any of the heat treatment conditions. However, after heat treatment at 1200°C for 5 hours, the evaluation sample SK(1,7) had a higher specific surface area than the comparative samples SK(1,0) and SK(0,7). Furthermore, even after heat treatment at 1200°C for 30 hours, the evaluation sample SK(1,7) was able to maintain a larger specific surface area than the comparative samples SK(1,0) and SK(0,7), confirming that the mixed addition of silica and barium oxide is effective in improving heat resistance. In addition, after heat treatment at 1200°C for 5 hours and 1200°C for 30 hours, the evaluation sample SK(1,7) had a higher specific surface area than the comparative sample SK(3,0), and SiO 2 It was confirmed that even when the addition rate was reduced from 3% by mass to 1% by mass, by adding an appropriate amount of barium oxide, a specific surface area larger than the specific surface area (corresponding to the standard specific surface area) of the comparison sample (corresponding to the standard porous alumina for comparison) to which only silica was added at 3% by mass could be obtained.

[0091] As shown in Fig. 9(A), before heat treatment, the θ-Al 2 O 3 and γ-Al 2 O 3 The peak of γ-Al was confirmed in SK(0,7) and SK(1,7). 2 O 3 and barium monoaluminate (BaO·Al 2 O 3 ) peaks As shown in Fig. 9(B), after heat treatment at 1200℃ for 5 hours, α-Al was completely formed in SK(0,0) and SK(1,0). 2 O 3 It was confirmed that the α-Al metastasis occurred in SK(0,7) and SK(1,7). 2 O 3 In addition to the peaks of barium monoaluminate and barium hexaaluminate (BaO 6Al 2 O 3 ) peak was confirmed. From Figure 9(C), after heat treatment at 1200°C for 30 hours, the same products were observed as after heat treatment at 1200°C for 5 hours. However, the α-Al peak of SK(1,7) 2 O 3 The peak intensity of α-Al is lower than that of the other comparative samples, and as shown in Fig. 8, the specific surface area is high even after heat treatment at 1200°C for 30 hours. This shows that the coexistence of silica and barium oxide is effective for the α-Al 2 O 3 It was revealed that this suppresses the formation of , and contributes to heat resistance.

[0092] From Fig. 11, SiO 2 SiO 2 having a specific surface area equal to or larger than the specific surface area (corresponding to the standard specific surface area) of the comparative sample SK(3,0) which is the standard porous alumina even after heat treatment at 1200°C for 30 hours, when the doping rate Xs is within the range of 0.7 mass% or more and 3 mass% or less and the BaO doping rate Xb is within the range of 0.5 mass% or more and 14 mass% or less. 2 It can be seen that the first effective range of the BaO doping rate Xs and the BaO doping rate Xb exists in a wide range (the area surrounded by the thick line frame in FIG. 11). 2When the BaO doping rate Xb increases from 0.5 mass % at the doping rate Xs, the specific surface area exceeds the reference specific surface area, reaches a maximum value, and then decreases to below the reference specific surface area. 2 It can be seen that the larger the addition rate Xs, the wider the gap becomes.

[0093] From Fig. 11, SiO 2 It can be seen that by setting the BaO doping rate Xb as shown below according to the doping rate Xs, the specific surface area after heat treatment at 1200°C for 30 hours can be maintained or improved in the range of 1 to 1.724 times that of the standard porous alumina. 2 Even if the doping rate Xs is reduced from 3 mass% to 0.7 mass%, when the BaO doping rate Xb is in the range of 5 mass%≦Xb≦10 mass%, the specific surface area is 1 to 1.034 times the standard specific surface area, and heat resistance almost equivalent to that of the standard porous alumina is possible. 2 Even if the doping rate Xs is reduced from 3 mass% to 1 mass%, when the BaO doping rate Xb is in the range of 3 mass%≦Xb≦10 mass%, the specific surface area is 1 to 1.414 times the standard specific surface area, and the heat resistance is almost equal to or higher than that of the standard porous alumina. 2 Even if the doping rate Xs is reduced from 3 mass% to 2 mass%, when the BaO doping rate Xb is in the range of 1 mass%≦Xb≦14 mass%, the specific surface area is 1 to 1.655 times the standard specific surface area, and the heat resistance is almost equal to or higher than that of the standard porous alumina. 2 When the doping rate Xs is 3 mass%, the specific surface area is 1.207 to 1.724 times the standard specific surface area when the BaO doping rate Xb is in the range of 0.5 mass%≦Xb≦14 mass%, and the heat resistance is 20% or more higher than that of the standard porous alumina. 2 When the BaO additive rate Xs is in the range of 1 to 3 mass %, by bringing the BaO additive rate Xb close to 5 mass %, an improvement in the specific surface area of ​​about 1.4 to 1.7 times the reference specific surface area can be obtained, enabling further improvement in heat resistance.

[0094] From the above, the specific surface area of ​​SiO2 that has a specific surface area equal to or larger than the standard specific surface area after heat treatment at 1200°C for 30 hours is 2 The first effective range of the additive rate Xs and the BaO additive rate Xb is approximately as follows: 0.7 mass%≦Xs<1 mass% and 5 mass%≦Xb≦10 mass%, or 1 mass%≦Xs<2 mass% and 3 mass%≦Xb≦10 mass%, or 2% by mass≦Xs≦3% by mass, and 1% by mass≦Xb≦14% by mass.

[0095] However, even if it is outside the first effective range, for example, SiO 2 The specific surface area of ​​the evaluation sample SK(3,0.5) with the BaO doping rate Xs of 3 mass% and the BaO doping rate Xb of 0.5 mass% is In the vicinity of the bold frame in FIG. 11, the specific surface area after heat treatment at 1200° C. for 30 hours may be larger than the reference specific surface area.

[0096] [2.4] Evaluation results of caulking resistance: The results of measuring the solid acid amount and solid base amount of one evaluation sample and five comparative samples prepared by the kneading method are shown in Figure 12. The evaluation sample and comparative samples used were SK(1,7), SK(0,0), SK(1,0), SK(3,0), SK(5,0), and SK(0,7).

[0097] FIG. 13 shows the results of measuring the solid acidity of the evaluation samples and the comparative samples prepared by the kneading method by increasing the number of samples. The number of samples was 15 for the evaluation samples and 9 for the comparative samples. 2 The ranges of the addition rate and the BaO addition rate are wide, 0≦Xs≦5 and 0≦Xb≦14.

[0098] From FIG. 12, in the comparative sample with a BaO addition rate Xb of 0 mass%, the SiO 2As the doping rate Xs increases, the amount of solid acid increases and the amount of solid base decreases. In contrast, in the evaluation sample SK(1,7) in which barium with a BaO doping rate Xb of 7 mass% was added, and the comparison sample SK(0,7), the same SiO 2 The amount of solid acid is reduced and the amount of solid base is increased compared to the comparative samples SK(1,0) and SK(0,0) with the addition rate of Xs. The amount of solid acid in the evaluation sample SK(1,7) is SiO 2 The solid acidity is reduced to a level equal to or lower than that of the comparative sample SK(0,0) in which the additive rate Xs and the BaO additive rate Xb are 0 mass %.

[0099] From Fig. 13, SiO 2 When the addition rate Xs is in the range of 0 mass% to 5 mass%, SiO 2 It was confirmed that, when the BaO doping rate Xs was the same, the amount of solid acid monotonically decreased as the BaO doping rate Xb increased from 0 mass% to 14 mass%. In addition, when the BaO doping rate Xb was in the range of 0 mass% to 14 mass%, when the BaO doping rate Xb was the same, the amount of solid acid monotonically decreased as the BaO doping rate Xb increased from 0 mass% to 14 mass%. 2 It was confirmed that the amount of solid acid monotonically increased as the addition rate Xs increased from 0 mass % to 5 mass %.

[0100] Furthermore, from FIG. 13, SiO 2 When the addition rate Xs is within the range of 3 mass% or less and the BaO addition rate Xb is within the range of 14 mass% or less, the solid acidity of this alumina is less than the solid acidity of the comparative sample SK(3,0), which corresponds to the standard porous alumina, and it is found that the coking resistance is improved compared to the standard porous alumina.

[0101] [2.5] Summary of evaluation results: 8 and 12, it can be seen that the evaluation sample SK(1,7) had an improved specific surface area and a reduced solid acidity after heat treatment at 1200°C for 5 hours and 1200°C for 30 hours compared to the comparison sample SK(3,0), which corresponds to the standard porous alumina. It was thus confirmed that the mixed addition of silica and barium oxide was effective in improving both heat resistance and coking resistance.

[0102] Furthermore, from Figs. 11 and 13, SiO 2 Within the range of the doping rate Xs being 3 mass% or less and the BaO doping rate Xb being 14 mass% or less, the specific surface area of ​​the present alumina after heat treatment at 1200°C for 30 hours is equal to or greater than the specific surface area (reference specific surface area) of the comparative sample SK(3,0), and the solid acidity of the present alumina is equal to or less than the solid acidity of the comparative sample SK(3,0). 2 It was found that the effective range of the addition rate Xs and BaO addition rate Xb exists in a wide range, and it was confirmed that the mixed addition of silica and barium oxide within the effective range is effective for both improving heat resistance and coking resistance. The effective range is the SiO 2 content in which the specific surface area of ​​the above-mentioned present alumina after heat treatment at 1200°C for 30 hours is equal to or greater than the reference specific surface area. 2 This is the first effective range of the additive rate Xs and the BaO additive rate Xb.

[0103] Furthermore, as is clear from FIG. 11, for the above-mentioned effective range, SiO 2 By narrowing the range of the additive rate Xs and the BaO additive rate Xb to 1 mass%≦Xs≦3 mass% and 3 mass%≦Xb≦10 mass%, the specific surface area of ​​this alumina after heat treatment at 1200°C for 30 hours is further increased, and the heat resistance is further improved while maintaining the coking resistance.

[0104] [3] Evaluation of heat resistance and coking resistance of this alumina prepared by the first type of impregnation method: [3.1] Preparation of evaluation samples and comparison samples: C20 from Nippon Light Metal was used as a ready-made porous alumina, and the target SiO 2 The above-mentioned processes in steps #I11 and #I12 were carried out using the TEOS solution and the barium nitrate aqueous solution in amounts corresponding to the additive rate and BaO additive rate, to obtain an evaluation sample of this alumina.

[0105] As a comparative sample, SiO 2 Only the additive rate is 0 mass%, only the additive rate of BaO is 0 mass%, SiO 2Three comparative samples were also prepared in which both the SiO and BaO addition rates were 0% by mass. 2 The impregnation process was performed without using a TEOS solution for the comparative sample with a 0% BaO addition rate, and without using a barium nitrate aqueous solution for the comparative sample with a 0% BaO addition rate. The evaluation samples and comparative samples are represented by the symbols SI (Xs, Xb). Xs is SiO 2 Xb indicates the BaO addition rate (mass%), and Xb indicates the BaO addition rate (mass%).

[0106] [3.2] Heat resistance evaluation results: Fig. 14 shows the results of measuring the specific surface area of ​​the evaluation samples and the comparative samples prepared by the first type of impregnation method after heat treatment at 1200°C for 30 hours. The number of samples was 20 for the evaluation samples and 3 for the comparative samples. 2 The ranges of the additive rate and the additive rate of BaO are 0≦Xs≦3 and 0≦Xb≦14.

[0107] From Figure 14, SiO 2 SiO 2 having a specific surface area equal to or larger than the specific surface area (corresponding to the standard specific surface area) of the comparative sample SI(3,0) which corresponds to the standard porous alumina even after heat treatment at 1200°C for 30 hours, in which the additive rate Xs is within the range of 0.7% by mass to 3% by mass and the additive rate Xb is within the range of 1% by mass to 14% by mass. 2 It can be seen that the second effective range of the doping rate Xs and the BaO doping rate Xb exists in a wide range (area surrounded by a thick line frame in FIG. 14). The second effective range coincides with the first effective range for the evaluation sample prepared by the kneading method shown in FIG. 11. In addition, the same SiO 2 At the BaO doping rate Xs, when the BaO doping rate Xb increases from 1 mass%, the specific surface area exceeds the reference specific surface area, reaches a maximum value, and then decreases to a value equal to or less than the reference specific surface area. The range of the BaO doping rate Xb where the specific surface area is equal to or greater than the reference specific surface area is SiO 2 The fact that the larger the doping rate Xs, the wider the band becomes also coincides with the measurement results shown in FIG.

[0108] Therefore, the explanation regarding the heat resistance of the evaluation sample prepared by the kneading method shown in FIG. 11 is also applicable to the evaluation sample prepared by the first type of impregnation method shown in FIG.

[0109] [3.3] Evaluation results of caulking resistance: FIG. 15 shows the measurement results of the solid acidity of the evaluation samples and the comparative samples prepared by the first type of impregnation method. The number of samples was 12 for the evaluation samples and 8 for the comparative samples. 2 The ranges of the addition rate and the addition rate of BaO are 0≦Xs≦5 and 0≦Xb≦20.

[0110] From Figure 15, SiO 2 When the addition rate Xs is in the range of 0 mass% to 5 mass%, SiO 2 Addition rate When Xs was the same, it was confirmed that the solid acid amount monotonically decreased as the BaO addition rate Xb increased from 0 mass% to 20 mass%, compared to the solid acid amount of the comparative sample with a BaO addition rate Xb of 0 mass%. In this way, the point where the solid acid amount monotonically decreased as the BaO addition rate Xb increased is consistent with the case of the evaluation sample prepared by the kneading method shown in FIG.

[0111] Furthermore, from FIG. 2 Within the range where the additive rate Xs is 3 mass% or less and the BaO additive rate Xb is 14 mass% or less, the solid acid amount of the alumina prepared by the first type impregnation method, as well as the evaluation sample prepared by the kneading method shown in FIG. 13, is less than the solid acid amount of the comparative sample SI(3,0) which corresponds to the standard porous alumina, and it is found that the coking resistance is improved compared to the standard porous alumina.

[0112] [3.4] Summary of evaluation results: 14 and 15, as in the evaluation samples prepared by the kneading method shown in FIGS. 11 and 13, the alumina prepared by the first type of impregnation method also had SiO 2Within the range of the doping rate Xs being 3 mass% or less and the doping rate Xb being 14 mass% or less, the specific surface area of ​​the present alumina after heat treatment at 1200°C for 30 hours is equal to or greater than the specific surface area (reference specific surface area) of the comparative sample SI(3,0), and the solid acidity of the present alumina is equal to or less than the solid acidity of the comparative sample SI(3,0). 2 It can be seen that the effective ranges of the addition rate Xs and the BaO addition rate Xb exist in a wide range. As a result, it was confirmed that the mixed addition of silica and barium oxide within the effective range is effective for both improving heat resistance and coking resistance. The effective range is the SiO 2 content range where the specific surface area of ​​the above-mentioned present alumina after heat treatment at 1200°C for 30 hours is equal to or greater than the reference specific surface area. 2 This is the second effective range of the BaO addition rate Xs and the BaO addition rate Xb.

[0113] As described above, regardless of the preparation method, SiO 2 In the same effective range of the additive rate Xs and the BaO additive rate Xb (same as the first and second effective ranges), the heat resistance and coking resistance can be improved by the mixed addition of silica and barium oxide. This is because the components contained in the sample sintered at 1000°C are the same whether the preparation method is the kneading method or the impregnation method. When the sample is sintered at 1200°C for a long time, the solid-phase reaction between silica and alumina, and between barium oxide and alumina begins. As mentioned above, when barium is added alone, the alpha-alumina of gamma-alumina is formed faster than the formation of barium hexaaluminate, which is the key to suppressing sintering, and the specific surface area is reduced by high-temperature heat treatment. Also, the addition of silica can delay the alpha-alumina to a certain extent in the early stage of sintering, but it cannot prevent the alpha-alumina from being formed during long-term sintering at 1200°C. On the other hand, by adding a mixture of silica and barium oxide, the silica delays the initial alpha-conversion, and the subsequent production of barium hexaaluminate inhibits the production of alpha-alumina, which is thought to result in a high specific surface area. These trends can be explained from Figures 8, 9, and 10.

[0114] [4] Another embodiment of the method for preparing the alumina: In the above embodiment, the kneading method, the first and second types of impregnation methods have been described as the method for preparing the present alumina. However, the method for preparing the present alumina can be carried out by any method other than SiO 2 As long as the doping rate and BaO doping rate can be precisely controlled, the method is not limited to a specific method. Other methods for preparing the present alumina include a precipitation method, a sol-gel method, and the like. The precipitation method is briefly described below.

[0115] [4.1] Preparation of this alumina by precipitation method: As shown in FIG. 16, the method for preparing the present alumina by the precipitation method can be roughly divided into a method for preparing an alkoxysilane solution containing an alkoxysilane, a mixed solvent containing water and an alcohol, and an inorganic acid, and a method for preparing an aluminum solution containing an aluminum compound and water by mixing an aqueous solution of a barium compound with an aluminum solution containing an aluminum compound and water. The method includes the steps of: preparing a mixed solution in which an aluminum compound, an alkoxysilane, and a barium compound are dissolved in a mixed solvent (Step #P1); coprecipitating aluminum hydroxide with a silicon compound in the mixed solvent to form a first precipitate (Step #P2); cooling the solution containing the precipitate to below 60°C and then adding ammonium carbonate to precipitate barium as a carbonate to form a second precipitate (Step #P3); and filtering and washing the precipitate containing the barium compound by suction filtration, and drying and calcining the filtered and washed precipitate to form a porous alumina containing aluminum oxide, silica, and barium oxide (this alumina) (Step #P4).

[0116] The alkoxysilane solution, aluminum solution, and aqueous solution of barium compound used in step #P1 are the same as the alkoxysilane solution, aluminum solution, and aqueous solution of barium compound used in step #K1 and step #K3 of the kneading method described above, and a duplicated description will be omitted. In addition, in FIG. 16, a TEOS solution is exemplified as the alkoxysilane solution, and an aqueous solution of barium nitrate is exemplified as the aqueous solution of barium compound. In addition, step #P2 is basically the same as step #K2 of the kneading method described above, and a duplicated description will be omitted. However, in step #P2, the barium compound does not co-precipitate with aluminum hydroxide and silicon compound as barium hydroxide, so step #P3 is required.

[0117] In step #P3, the solution containing the precipitate is cooled to 60°C or lower in order to avoid decomposition of ammonium carbonate, which decomposes into carbon dioxide gas, ammonia, and water at temperatures above 60°C.

[0118] [5] Modifications of this alumina: The present alumina can be prepared by, for example, the kneading method, impregnation method, precipitation method, or the like described above, by converting SiO 2 This is a porous alumina in which two oxides, silica and barium oxide, are mixed and added to the alumina prepared so that the SiO and BaO addition rates are within the above-mentioned effective ranges. 2 The addition rate and the BaO addition rate are on average within the above-mentioned effective range.

[0119] However, SiO 2In the case where a different type of porous alumina (such as alumina alone, porous alumina to which only silica has been added, porous alumina to which only barium oxide has been added, porous alumina to which silica and barium oxide have been added, porous alumina to which silica and an oxide other than barium oxide have been added, etc.) in which the doping rate and BaO doping rate are not within the above-mentioned effective range is mixed with the present alumina and exists partially or locally, if the amount of SiO 2 Even if the BaO content and BaO content are outside the effective ranges on average, if the present alumina exists separately from the heterogeneous porous alumina and has the desired properties (specific surface area and solid acidity after heat treatment at 1200°C for 30 hours), the portion present as the present alumina can naturally achieve the desired effect of providing a porous alumina with excellent heat resistance and coking resistance. Therefore, as one embodiment of the present alumina, the present alumina can take a form in which the above-mentioned heterogeneous porous alumina exists partially or locally.

[0120] Furthermore, the present alumina is SiO 2 As long as the doping rate and BaO doping rate are within the above-mentioned effective range and the desired properties (specific surface area and solid acidity after heat treatment at 1200°C for 30 hours) are obtained, components other than silica and barium oxide (oxides, etc.) may be added to alumina in small amounts compared to silica and barium oxide.

[0121] [6] Application examples of this alumina: As described above, this alumina has excellent heat resistance, and therefore it is suitable for use as a catalyst supporting catalytically active components. It is useful as a catalyst carrier, a filter, etc. Furthermore, since the present alumina has excellent heat resistance as described above and also excellent coking resistance, it is suitable as a catalyst carrier used in reactions using hydrocarbons, such as steam reforming reactions. [Industrial Applicability]

[0122] The present invention is preferably used for porous alumina in which silica and barium oxide are added to aluminum oxide, and for a catalyst using the porous alumina as a carrier.

Claims

1. Aluminum oxide (Al 2 O 3 ) to silica (SiO 2 ) and barium oxide (BaO) are added, The barium oxide is barium monoaluminate (BaO.Al 2 O 3 ) or as barium monoaluminate (BaO.Al 2 O 3 ) and barium hexaaluminate (BaO.6Al 2 O 3 ) The aluminum oxide and SiO 2 The amount of SiO relative to the total mass of the added amount 2 The ratio of the added amount is SiO 2 The addition rate (mass%) is The aluminum oxide and the SiO 2 The ratio of the amount of BaO added to the total amount of added BaO is defined as the BaO addition rate (mass%). The SiO 2 The amount of addition is determined by dividing the content of silicon (Si) in the porous alumina by the amount of SiO 2 This is the amount converted into the content of The BaO content is the amount obtained by converting the content of barium (Ba) in the porous alumina into the content of BaO, The SiO 2 The BaO content is in the range of 3 mass% or less, and the BaO content is in the range of 14 mass% or less. The specific surface area of ​​the porous alumina measured by a predetermined measuring method after heat treatment at 1200° C. for 30 hours is 2 The specific surface area of ​​the porous alumina was determined so as to be equal to or larger than the specific surface area of ​​the standard porous alumina for comparison, which was prepared by the same preparation method except that the BaO content was set to 3 mass % and the BaO content was set to 0 mass %. A porous alumina, characterized in that said silica and said barium oxide are added to said aluminum oxide.

2. The SiO 2 The additive rate is in the range of 0.7% by mass or more and 3% by mass or less, and the BaO additive rate is in the range of 14% by mass or less, so that the specific surface area of ​​the porous alumina is equal to or greater than the reference specific surface area.

2. The porous alumina according to claim 1, wherein said aluminum oxide is doped with said silica and said barium oxide.

3. The SiO 2 The BaO addition rate is in the range of 3 mass% or less or in the range of 0.7 mass% to 3 mass%, and the BaO addition rate is in the range of 0.5 mass% to 14 mass%, so that the specific surface area of ​​the porous alumina is equal to or greater than the reference specific surface area.

2. The porous alumina according to claim 1, wherein said aluminum oxide is doped with said silica and said barium oxide.

4. Aluminum oxide (Al 2 O 3 ) to silica (SiO 2 ) and barium oxide (BaO) are added, The barium oxide is barium monoaluminate (BaO.Al 2 O 3 ) or as barium monoaluminate (BaO.Al 2 O 3 ) and barium hexaaluminate (BaO.6Al 2 O 3 ) The aluminum oxide and SiO 2 The amount of SiO relative to the total mass of the added amount 2 SiO specified by the ratio of added amount 2 The addition rate (mass%) is Xs (mass%), where 2 The amount of addition is determined by dividing the content of silicon (Si) in the porous alumina by the amount of SiO 2 This is the amount converted into the content of The aluminum oxide and the SiO 2 When the BaO addition rate (mass%) defined as the ratio of the BaO addition amount to the total mass of the addition amounts is Xb (mass%), the BaO addition amount is the amount obtained by converting the content of barium (Ba) in the porous alumina into the content of BaO, 0.7% by mass≦Xs<1% by mass and 5% by mass≦Xb≦10% by mass, or 1 mass%≦Xs<2 mass% and 3 mass%≦Xb≦10 mass%, or 2% by mass≦Xs≦3% by mass, and 1% by mass≦Xb≦14% by mass, The porous alumina is characterized in that

5. A steam reforming catalyst comprising the porous alumina according to any one of claims 1 to 4 and a catalytic substance supported on the porous alumina.

Citation Information

Patent Citations

  • Mesoporous composite oxides and catalyst as well as preparation method and aromatization method thereof

    CN101462050A

  • Improved catalyst for manufacturing methylamine

    JP1982171436A

  • Heat resistant catalyst and its production

    JP1988119851A

  • Production of heat resistant alumina complex oxide

    JP1988242917A

  • Porous alumina material, process for producing same, and catalyst

    WO2012096386A1